Penyuluhan Regulasi dan Pembekalan Strategi Pemasaran serta Pengembangan UMKM pada Pedagang Kaki Lima Di Lapangan Kantin Wirabraja Kota Bukittinggi (Jurnal Suluah Komunitas, 2022)
The presence of street vendors (PKL) can sometimes unsettle residents and the government, but their presence can also contribute to driving the economy of an area. The lack of resources and knowledge regarding regulations and provision of strategies in business development by street vendors makes their business less developed. The assistance activities for street vendors are expected to be useful for business continuity and gain knowledge in entrepreneurship. There are 100 street vendors in the Wirabraja Kantin Square, Bukittinggi City, consisting of culinary traders specializing in local wisdom, food stalls, clontongan goods, traditional cakes, martabak, various fried foods, bakery shops, burgers, chicken meatball noodles, vegetable traders, fruit sellers. , soft drinks, household furniture, construction equipment, soles. Assistance in Counseling on Regulations and Debriefing on Marketing Strategy and MSME Development for Street Vendors so that later they understand regulations and are able to manage business financial management, so that financial reports on business results are recorded properly, assistance in marketing business results so that there are more buyers, assistance in using technology information, so that street vendors can compete with other traders